Romantic Relationship Satisfaction and Parent-Infant Bonding During the Transition to Parenthood: An Attachment-Based Perspective - Little, Kathleen K.; Sockol, Laura E. (Frontiers in Psychology, 2020)
An important element of well-being during the transition to parenthood is new parents’ relationships with their partners and babies. Attachment theory posits that early caregiving experiences influence close relationships throughout the lifespan. Disruptions to the parent-child relationship, such as parental divorce or separation, may therefore have intergenerational effects as adult children of divorce navigate changes in their later relationships. This study examined whether new parents who have experienced a divorce or separation in their family of origin report greater romantic relationship dissatisfaction or impairment in the parent-infant bond during the early postpartum period, and if these associations are mediated by adult attachment. First-time parents of infants through 6 months of age (N = 94) completed measures of adult attachment, romantic relationship satisfaction, and parent-infant bonding. New parents who had experienced parental divorce or separation did not differ from those from intact families with regard to romantic relationship satisfaction, parent-infant bonding, attachment anxiety, or attachment avoidance. Attachment anxiety and avoidance were both associated with romantic relationship dissatisfaction and greater impairment in the parent-infant bond. These findings suggest that the experience of parental divorce or separation, in and of itself, does not confer increased risk for negative relational outcomes among new parents. Securely attached adults, regardless of their own parents’ marital status, report more positive relationships with their partners and infants during the early postpartum period.